A Game-Based Vocabulary App for EFL Learners: Design and Development Study - Tri Wahyuni Floriasti; Nindya Hikmah Meliarany (Universitas Muhammadiyah Jember, 2026)
A game-based vocabulary application for junior high school students studying English as a foreign language (EFL) was the goal of this project. Seven stages were used in the study, which used a Research and creation (R&D) technique modified from the Jolly and Bolitho model: needs analysis, design of the syllabus and course grid, product creation, expert validation, revision, and implementation. Questionnaires, expert reviews, and classroom observations were used to gather data. The Android app featured interactive games, quizzes, audio-visual resources, and vocabulary lists. It was created with Smart Apps Creator and Canva. The app received a